Effects of stressful life events on ART treatment outcomes: a prospective study on the role of individual and personality characteristics and psychological health conditions - Maria Clelia Zurlo; Federica Vallone; Maria Francesca Cattaneo Della Volta (Frontiers in Psychology, 2026)
Background Infertility research highlighted that early exposure to stressful life events (SLEs) and childhood adversities are significantly associated not only with women’s psychological health, but also with outcomes of assisted reproductive technologies. Nevertheless, there is a lack of studies adopting a multidimensional and transactional approach exploring how early life and family-related stressors potentially influence treatment outcomes through multiple interacting variables. Objective The present study aimed to test the associations between stressful life events and ART treatment outcomes (Failure/Success) by also exploring the potential mediating role of psychological health conditions (State-Anxiety and Depression) and the moderating role of socio-demographics, infertility-related parameters, and personality characteristics. Methods A prospective study was conducted. At the beginning of ART treatment (T1, 2020), 130 infertile women completed self-report measures assessing individual (socio-demographics) and personality (coping strategies) characteristics, fertility-related parameters, SLEs (In Family Pre-existing Pregnancy Difficulties; Problems in Family of Origin; Health Problems in Childhood), and psychological health conditions (State-Anxiety/Depression). After 5 years (T2, 2025), medical records were reviewed to verify treatment outcomes. Main/mediating/moderating hypotheses were tested by using Correlational-Analyses and Hayes-PROCESS-tool. Results In Family Pre-existing Pregnancy Difficulties was found both directly and indirectly associated, partially via Depression, to ART treatment outcome, while the impact of Problems in Family of Origin and Health Problems in Childhood was fully mediated by Depression. Avoidant coping strategies were found to be a significant moderator exacerbating the negative impact of In Family Pre-existing Pregnancy Difficulties on Depression. Conversely, higher educational levels, along with the adoption of positive attitude and social support coping strategies, played significant buffering moderation roles, acting as pivotal resources. Conclusion These findings underscore the influence of stressful life events on ART outcomes via women’s depressive symptomatology and the role of specific moderating variables that should be addressed through routine psychological screening and multidisciplinary counselling interventions in ART centers to enhance both mental health and treatment success for infertile women.